Day Case Tonsillectomy in Children - Humadi, Ahmed (AL-Kindy College Medical Journal, 2013)
Background: Day case surgery has become widely accepted as a safe alternative to the inpatient care in up to 70% of the cases at a children’s hospital. It has the advantage of minimizing the psychological trauma of hospitalization, decreasing nosocomial infection, less costly and frees up hospital beds.Objectives: To assess the advantages and disadvantages of this type of surgery.Methods: this is a prospective study, in which two hundred thirty childhood tonsillectomies were performed as a day-case in the department of otolaryngology at Al Shaheed Gazi hospital, Medical City Complex during the period from October 2009 to September 2010. The patients age range from 3-12 years (Mean 7.2 years).Results: 46.08% males and 53.91% females were included. A total of two hundred twenty three patients were discharged home six hours after the operation. It's found that the incidence of reactionary hemorrhage was 0.8% and the cases presented within 5 hours after leaving the theater. In 99.2% of cases, there was no evidence of serious reactionary hemorrhage.Conclusions: day case tonsillectomy in children is likely to be safe if the patients are discharged after 6 hours period of postoperative observation in day-case unit.